Lead-acid battery desulfation using a high-frequency pulse desulfator in standalone PV systems - El Filali, Anas; Laadissi, El Mehdi; Khalfi, Jaouad; Zazi, Malika (International Journal of Applied Power Engineering (IJAPE), 2024)
The work presented in this article contributes to the study of a standalone photovoltaic (PV) system with battery storage by creating an electronic board that allows for the recovery of the battery's capacity using pulse technology that uses high-energy pulses from the PV panel to break down and remove the sulfation buildup, which is a contributing factor in the failure of most lead-acid batteries. Different methods or treatments can be used to lessen the impact of sulfation or even get rid of it and achieve battery rejuvenation. Battery sulfation is a process in which sulfate crystals form on the plates of a lead-acid battery, impeding its ability to retain a charge, and decreasing the battery’s overall effectiveness. This process can happen due to various reasons, such as charging for a shorter time than required, charging for a longer period of time than required, or even not charging it for quite some time. Sulfation affects a battery’s lifespan and comes with adverse effects on its performance, though it can be prevented.